Impact of Alkali Metals on CeO2-WO3/TiO2 Catalysts for NH3-Selective Catalytic Reduction and Lifetime Prediction of Catalysts - Mutao Xu; Yuhang Deng; Xingxiu Gao; Qijie Jin; Wei Yan; Liguo Chen; Jian Yang; Jing Song; Changcheng Zhou; Haitao Xu (Molecules)
Ce-based catalysts have been widely used in the removal of nitrogen oxides from industrial flue gas because of their good catalytic performance and environmental friendliness. However, the mechanism of alkali metal poisoning in Ce-based catalysts remains to be further studied. This work involves the preparation of the K/Na-poisoned CeWTi catalyst via the impregnation method for assessing its performance in NO removal. Experiments show that both K and Na exhibit detrimental effects on the CeWTi catalyst, and the loading of alkali metal reduces the specific surface area and pore volume of the catalyst. Furthermore, the presence of alkaline metals results in a notable decline in the CeWTi acid concentration, particularly in Lewis acid sites. Concurrently, the levels of Ce3+, oxygen vacancies, and reducing agents on the catalyst surface decrease, leading to diminished reduction capability and eventual catalyst deactivation. The application of a BP neural network for catalyst activity prediction yielded an average relative error of approximately 0.73%, indicating enhanced accuracy in prediction outcomes. This work explored the cause of alkali metal poisoning of the CeWTi catalyst and provided an effective prediction method for the lifetime of CeWTi catalyst, which provided theoretical guidance for the engineering application of Ce-based catalysts.